Drug policy and the public good - Babor, Thomas F. (Oxford University Press)
Framing the issues -- Matters of substance -- The international dimensions of drug use -- Harms associated with illicit drug use -- Illegal markets : the economics of drug distribution and social harm -- The legal market : prescription and diversion of psychopharmaceuticals -- Strategies and interventions to reduce drug use and related harm : section overview -- Preventing illicit drug use by young people -- Health and social services for drug users -- Supply control -- Criminalization and decriminalization of drug use or possession -- Prescription regimes and other measures to control misuse of psychopharmaceuticals -- Drug policy and control at the international level -- The variety of national drug policies -- Health and social services for drug users : systems issues -- Summary and conclusions